PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION (LSQ) DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS XI IIS SMAN 16 PADANG - Eliza, Seprina - (STKIP PGRI Sumbar, 2014)
The studentsâ learning achievement in mathematics was still low. The students whotended to be quiet, be unwilling to ask questions and expressing ideas on somethingunclear, had less responsibility and skill to learn were assumed as the causes of thisproblem. The purpose of this research was to reveal whether the use of LearningStarts with a Question (LSQ) active learning strategy affected the studentsâ learningachievement, and what the studentsâ attitude toward and their skills are after thestrategy applied in class XI IIS of SMAN 16 Padang. This was a pre-experimentalresearch which used pretest and post-test group design. The population of theresearch was the students in class XI IIS of SMAN 16 Padang. Of the sample, classXI IIS 1 was taken as the sample. The gotten was analyzed by using t-test in whichthe value of tcalculated (26,86) was bigger than ttable (2,08) and was 0,05. The resultof the observation indicated that the average score of the studentsâ attitude was 3,01and their skill was 2,94. Hance , it was concluded that the use of Learning Startswith a Question (LSQ) active learning strategy affected the studentsâ learningachievement, the studentsâ attitude had been good, and their learning skill improved.